The influence of confirmatory psychology on consumers' purchase of sports goods on an e-commerce platform - Chunmei Liu; Shaohui Ma; Longhui Cao , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study examines the impact of confirmatory psychology (CP) on the e-commerce (EC) platform purchasing of sporting products by consumers. The evolution of network communication technologies has produced EC. This study used literature and mathematical statistics to assess the consumption data of sports products purchased by consumers who purchase sports products. By descriptive analysis, variables such as CP are partitioned into dimensions, and hypotheses regarding the relationship between variables are formulated. The study found significant positive associations (P< 0.01) between normative conformity and customers' purchase intentions and between informational conformity and consumers' buying intentions. The interaction variable significantly benefits purchase intent (coefficient standard = 0.045, P< 0.001). Interaction elements showed a statistically significant positive impact on purchase intent (coefficient standard = 0.18, P <0.001). The study has theoretical ramifications that contribute to the body of knowledge. Moreover, the practical consequences of this research are essential for improving the EC platform offerings.